2016
DOI: 10.1016/j.cois.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic functions of extraembryonic membranes in insects

Abstract: Morphogenetic functions of the amnioserosa, the serosa, the amnion, and the yolk sac are reviewed on the basis of recent studies in flies (Drosophila, Megaselia), beetles (Tribolium), and hemipteran bugs (Oncopeltus). Three hypotheses are presented. First, it is suggested that the amnioserosa of Drosophila and the dorsal amnion of other fly species function in a similar manner. Second, it is proposed that in many species with an amniotic cavity, the amnion determines the site of serosa rupture, which, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
1
40
1
Order By: Relevance
“…Similar interactions between yolk sac and extraembryonic tissue have been reported previously in D. melanogaster, albeit at later stages of development, where they contribute to germband retraction and dorsal closure (Goodwin et al, 2016;Narasimha and Brown, 2004;Reed et al, 2004;Schöck and Perrimon, 2003). More generally, interactions of yolk sac and overlying epithelia have been long implicated in insect as well as vertebrate development (Anderson, 1972a;Anderson, 1972b;Bruce, 2016;Counce, 1961;Schmidt-Ott and Kwan, 2016), suggesting that yolk sac dependent regulation of serosa spreading in the M. abdita embryo may reflect a more common phenomenon.…”
Section: Abdita Serosa Spreading Proceeds In Distinct Phasessupporting
confidence: 56%
See 2 more Smart Citations
“…Similar interactions between yolk sac and extraembryonic tissue have been reported previously in D. melanogaster, albeit at later stages of development, where they contribute to germband retraction and dorsal closure (Goodwin et al, 2016;Narasimha and Brown, 2004;Reed et al, 2004;Schöck and Perrimon, 2003). More generally, interactions of yolk sac and overlying epithelia have been long implicated in insect as well as vertebrate development (Anderson, 1972a;Anderson, 1972b;Bruce, 2016;Counce, 1961;Schmidt-Ott and Kwan, 2016), suggesting that yolk sac dependent regulation of serosa spreading in the M. abdita embryo may reflect a more common phenomenon.…”
Section: Abdita Serosa Spreading Proceeds In Distinct Phasessupporting
confidence: 56%
“…Our time-lapse recordings and previously published Mab-egr expression indicated that the M. abdita amnion developed as an open and mostly lateral tissue. The tissue topology of the amnion in M. abdita was thus markedly different than the closed and ventral amnion that has been reported for non-cyclorrhaphan flies and most other insects (Panfilio, 2008;Schmidt-Ott and Kwan, 2016). Connected to the lateral amnion, the amnion at the posterior end of the germband consisted of more cells and closed over the ventral midline of the embryo proper.…”
Section: Abdita Forms An Open Lateral Amnionmentioning
confidence: 60%
See 1 more Smart Citation
“…High levels of BMP signaling, centered on the dorsal midline, specify a single extraembryonic tissue, the amnioserosa. However, in basal-branching flies, including Megaselia abdita (Phoridae), BMP signaling specifies two extraembryonic tissues, the serosa and the amnion (Schmidt-Ott and Kwan, 2016). Previously, we showed that the dynamics of BMP signaling in the blastoderm are similar between Megaselia and Drosophila , but differ in the early gastrula when the Megaselia gradient broadens while the Drosophila gradient remains static (Rafiqi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This dearth of laboratory models is even more acute in the case of early branching groups of insects that correspond to the first representatives of the crucial biological and ecological transitions mentioned above. Such transitions are for instance, key adaptations to terrestrial life such as the development of the extraembryonic tissue amnion and serosa [1418], the establishment of early embryo segmentation mechanisms and the transition from short-to long-germ band embryos [1923], the basal organization of the head [24, 25], or the origin of wings and the capacity to fly (an issue that is currently hotly debated [26–34]). Overall, what these examples reveal ultimately is the need of developing and establishing new model systems, in particular around the nodes of the tree where these key novelties originated.…”
Section: Introductionmentioning
confidence: 99%